Fossil and friction free : A critical discourse analysis of sustainability in EU freight policy - Gratorp, Christina (Environmental Politics, 2025)
Policy on greening freight constitutes a recent addition to the discourse on sustainability in the EU. To stimulate economic growth, the EU also plans for freight transport activity to grow significantly over the coming decades. In this paper, drawing on critical discourse analysis and Marxian geographical thought, I show how the argument for implementing sustainable freight is constructed in EU freight policy and analyse its contribution to capital reproduction. I find a dominating argument that, by promoting green expansion legitimized by clean technologies, underpins actions that reshape geographies to the demands of circulation, commerce and trade while reproducing conditions of crisis. Thus, EU freight policy harbors contradictions between sustainability and growth that are only discursively resolved.